Effect of the presence of HCl on simultaneous CO2 capture and contaminants removal from simulated biomass gasification producer gas by CaO-Fe2O3 sorbent in calcium looping cycles - Dashtestani, Forogh; Nusheh, Mohammad; Siriwongrungson, Vilailuck; Hongrapipat, Janjira; Materic, Vlatko; Yip, Alex C.K.; Pang, Shusheng (My University, 2021)
This study investigated the effect of HCl in biomass gasification producer gas on the CO2 capture efficiency and contaminants removal efficiency by CaO-Fe2O3 based sorbent material in the calcium looping process. Experiments were conducted in a fixed bed reactor to capture CO2 from the producer gas with the combined contaminants of HCl at 200 ppmv, H2S at 230 ppmv, and NH3 at 2300 ppmv. The results show that with presence of HCl in the feeding gas, sorbent reactivity for CO2 capture and contaminants removal was enhanced. The maximum CO2 capture was achieved at carbonation temperatures of 680◦C, with efficiencies of 93%, 92%, and 87%, respectively, for three carbonation-calcination cycles. At this carbonation temperature, the average contaminant removal efficiencies were 92.7% for HCl, 99% for NH3, and 94.7% for H2S. The outlet contaminant concentrations during the calcination process were also examined which is useful for CO2 reuse. The pore structure change of the used sorbent material suggests that the HCl in the feeding gas contributes to high CO2 capture efficiency and contaminants removal simultaneously.
Keywords: Calcium looping; CaO-Fe2O3 sorbent; CO2 capture; Contaminant removal